Characteristics of Mathematical Modeling Module on Seawater Boiling Point Elevation - Ni Nyoman Ariyani; Desi Desi (EduChemia: Jurnal Kimia dan Pendidikan, 2026)
Students often treat chemistry and mathematics as separate subjects when they learn colligative properties, using mathematics mainly as a calculation tool rather than for conceptual understanding. This separation limits their ability to connect mathematical reasoning with chemical concepts and engage in sensemaking. Although model-based instruction can support such integration, it is rarely implemented in classroom practice or presented in chemistry textbooks. This gap underscores the need for a model-based module. Accordingly, this study aimed to develop and characterize a mathematical modeling module for seawater boiling point elevation, focusing on its content quality, chemistry-mathematics integration, and alignment with the mathematical modeling cycle. This study employed a development research design incorporating Tessmer’s formative evaluation framework, encompassing analysis, design, development, and formative evaluation stages. Data were collected through needs analysis, expert review involving six experts (chemistry content, mathematical modeling and interdisciplinary integration), and one-to-one evaluation with three students of different levels of achievement. The findings indicate that the module demonstrates good content quality (mean = 2.70), strong alignment with the modeling cycle (mean = 2.78), and high chemistry-mathematics integration (mean = 2.95). Overall, the module shows promise as an instructional resource to promote interdisciplinary connections and strengthen students’ quantitative reasoning in learning colligative properties.